MEF2C haploinsufficiency syndrome: A severe neurodevelopmental disorder with variable epilepsy - Paciorkowski, Alex R.; Porter, Brenda E. (Journal of Pediatric Epilepsy, 2012)
MEF2C haploinsuffiency syndrome is one of several recently identified conditions that have abnormalities in multiple areas of neurologic function. Infant-onset myoclonic seizures and infantile spasms are common, but later-onset forms of epilepsy have been reported as well. Most children have a hyperkinetic movement disorder consisting of frequent stereotypies that aid in clinical recognition of the syndrome. There is evidence that MEF2C is a member of several key neurodevelopmental genetic pathways, and the hope is that in the future one or more of these pathways may be amenable to pharmacologic modification with the goal of symptom improvement.
Keywords: MEF2C haploinsufficiency; infantile spasms; infant myoclonic epilepsy; hyperkinesis